Rozwiąż równanie :
(x-1)² /2 – (3x – 4)²/14=(4 - x)(4 + x)/7
rozwiąż nierówność :
2(x-6)² - (x - 8)²≥ x(x - 4)

są to zadania z matematyki z plusem 2 (30/91 i 31/91)
wzory :
(a + b)² = a² + 2ab + b²
(a - b)² = a² - 2ab + b²
(a + b)(a - b) = a² - b²

z góry dziękuje :):)

2

Odpowiedzi

2009-12-05T19:43:54+01:00
2009-12-06T00:34:50+01:00
Witaj:)
(x-1)² /2 – (3x – 4)²/14=(4 - x)(4 + x)/7
pomnozmy wszystko przez 14 aby zlikwidowac ulamki
7(x-1)²-(3x-4)²= 2(4 - x)(4 + x)
7( x²-2x+1)-( 9x²-24x+16)=2(16-x²)
7 x²-14x+7-9 x²+24x-16=32-2 x²
7 x²-14x+7-9 x²+24x-16-32+2x²=0
10x-41=0
10x=41
x=41/10
x=4 i 1/10


zad 2
2(x-6)² - (x - 8)²≥ x(x - 4)
2(x²-12x+36)-(x²-16x+64)≥x² -4x
2x²-24x+72-x²+16x-64-x²+4x≥0
-4x+8≥0
-4x≥-8
x≤2

x nalezy (-∞;2>

1 5 1